Descent into chaos : the U.S. and the disaster in Pakistan, Afghanistan, and Central Asia - Rashid, Ahmed. (Penguin Books, 2009)
Examines how the failure of the nation building policies of the United States have contributed to increased instability in both Pakistan and Afghanistan, a result which represents the greatest threat to peace and security in the global community.